Exercise Induces White Adipose Tissue Browning Across the Weight Spectrum in Humans - Otero-Díaz, Berenice; Rodríguez-Flores, Marcela; Sánchez-Muñoz, Verónica; Monraz-Preciado, Fernando; Ordoñez-Ortega, Samuel; Becerril-Elias, Vicente; Baay-Guzmán, Guillermina; Obando-Monge, Rodolfo; García-García, Eduardo; Palacios-González, Berenice; Villarreal-Molina, María Teresa; Sierra-Salazar, Mauricio; et al. (Frontiers in Physiology, 2018)
While the effect of exercise on white adipose tissue browning and metabolic improvement in rodents is clear, there are few studies in humans with inconclusive results. Thus, the aim of the study was to assess whether an exercise intervention promotes subcutaneous adipose tissue browning in humans, and whether this response is associated with metabolic improvement in three groups of individuals defined by BMI. Sedentary adult subjects with different BMI were enrolled in a 12-week bicycle training program. Brown and beige gene expression in subcutaneous adipose tissue (scWAT) biopsies, and serum glucose, insulin, lipid, adipokine and myokine levels were compared before and after the exercise intervention. Thirty-three non-diabetic subjects (mean age 30.4 ± 4.6 years; 57.57% female; 13 normal weight, 10 overweight and 10 with obesity) completed the exercise intervention. Without any significant change in body composition, exercise improved several metabolic parameters, most notably insulin resistance and particularly in the overweight group. Circulating adiponectin, apelin and irisin exercise-induced changes predicted 60% of the insulin sensitivity improvement. After exercise UCP1, TBX1, CPT1B scWAT expression significantly increased, along with P2RX5 significant positive staining. These changes are compatible with scWAT browning, however they were not associated with glucose metabolism improvement. In conclusion, 12-weeks of exercise training produced brown/beige gene expression changes in abdominal scWAT of non-diabetic individuals with different BMI, which did not contribute to the metabolic improvement. However, this result should not be interpreted as a lack of effect of browning on metabolic parameters. These findings suggest that a bigger effect is needed and should not preclude the development of more effective strategies of browning. Furthermore, exercise-induced changes in adiponectin, apelin and irisin predicted insulin sensitivity improvement, supporting the important role of adipokines and myokines in metabolism homeostasis.